PERFORMANCE MANAGEMENT – A BASIC INSTRUMENT FOR SUSTAINABLE DEVELOPMENT OF POMICULTURE - DOBROVOLSCHI, Ludmila (Economy and Sociology, 2021)
Fruit growing has become an area of great interest for economic agents. Recently, it has been more difficult for the businesses to enter the market, which requires differentiation in management activity. In this sense, formulating the role of performance management in terms of consumer behaviour becomes a trampoline for effective management actions. In the scientific literature, it is given a minor attention, as evidenced by the low degree of research in the field of efficient management and of the sustainable development of fruit growing. Under these circumstances, the need to study the performance management as a basic tool in the sustainable development of fruit growing of the Republic of Moldova is more than adequate. Thus, the main objective of this article is the conceptual approach of advanced management – as a basic tool in the sustainable development of fruit growing. The informative basis of the investigation consisted of the consulted bibliographic sources, on the basis of which the author presented his own visions. The main research methods used were: monographic method, analysis, scientific observation, comparison, induction, deduction, explanation and interpretation. The obtained results highlighted: defining the notion of performance management, identifying its characteristics, specific functions and basic levers; value chain determination methodology and the impact of the developed value chain on the process of identifying export markets for Moldovan fruit.